Pengembangan Sistem Informasi Manajemen Pemesanan Berbasis Website di UMKM Nenda Print - Kunti Eliyen; Abidatul Izzah; Ellya Nurfarida; Lely Indah Kurnia; Agustono Heriadi; Dwi Rahma Fitriani (LKP Unity Academy, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, but they often face challenges in managing order and financial data due to manual recording. This study aims to develop a website-based order and profit data recording information system for Nenda Print MSMEs to improve business management efficiency. The system development method includes needs analysis, system design, implementation, testing, and evaluation. The developed website-based system is equipped with features for customer data management, order recording, financial transaction recording, automatic profit calculation, and real-time presentation of reports and graphs. Test results show that the system is able to simplify the data recording process, reduce the risk of data loss, and accelerate sales and profit calculations.